The University EFL Students’ Perceptions of QuillBot as an AI-Based Tool for Enhancing Paraphrasing Skills and Academic Writing in English - Amara, Rafika; Rahmah, Leny Saili; Ruswandi , Riki (FKIP - Universitas Riau, 2025)
This study investigates English as a Foreign Language (EFL) learners' perceptions of QuillBot, an artificial intelligence (AI) tool supporting academic writing and paraphrasing. The study was carried out at Universitas Islam Nusantara, with active students from the English Education Department in the sixth and eighth semesters. The data was collected using a validated questionnaire with 11 items and a Cronbach's alpha reliability coefficient of 0.792. The data indicate that QuillBot is well liked for its time- saving features, accessibility, and psychological benefits such as increased self-confidence and reduced paraphrase anxiety. Over 80% of respondents reported increased comfort in using the tool, nearly 89% acknowledged time efficiency, and more than 88% agreed on its ease of use. Furthermore, QuillBot helped to increase vocabulary, sentence organization, and writing coherence. More than half of the participants plan to continue using QuillBot for their academic writing tasks.These findings emphasize the importance of integrating AI technology into English language instruction to effectively improve students' writing skills.